IFN-gamma exposes a cryptic cytotoxic T lymphocyte epitope in HIV-1 reverse transcriptase. - Sewell, A; Price, D; Teisserenc, H; Booth, B; Gileadi, U; Flavin, F; Trowsdale, J; Phillips, R; Cerundolo, V (1999)
The proteasome, an essential component of the ATP-dependent proteolytic pathway in eukaryotic cells, is responsible for the degradation of most cellular proteins and is believed to be the main source of MHC class I-restricted antigenic peptides for presentation to CTL. Inhibition of the proteasome by lactacystin or various peptide aldehydes can result in defective Ag presentation, and the pivotal role of the proteasome in Ag processing has become generally accepted. However, recent reports have challenged this observation. Here we examine the processing requirements of two HLA A*0201-restricted epitopes from HIV-1 reverse transcriptase and find that they are produced by different degradation pathways. Presentation of the C-terminal ILKEPVHGV epitope is impaired in ME275 melanoma cells by treatment with lactacystin, and is independent of expression of the IFN-gamma-inducible proteasome beta subunits LMP2 and LMP7. In contrast, both lactacystin treatment and expression of LMP7 induce the presentation of the N-terminal VIYQYMDDL epitope. Consistent with these observations we show that up-regulation of LMP7 by IFN-gamma enhances presentation of the VIYQYMDDL epitope. Hence interplay between constitutive and IFN-gamma-inducible beta-subunits of the proteasome can qualitatively influence Ag presentation. These observations may have relevance to the patterns of immunodominance during the natural course of viral infection.